2018
DOI: 10.1109/jphot.2018.2848947
|View full text |Cite
|
Sign up to set email alerts
|

Single LED-Based Indoor Positioning System Using Multiple Photodetectors

Abstract: This paper presents a visible light positioning system using a single light-emitting diode (LED) and a novel receiver. In the proposed system, the receiver is composed of a horizontal photodetector (PD) and two tilted PDs, and a known calibration point is deployed to improve the accuracy of the positioning. Based upon the multi-PDs' relative positions and the received signal strength, the location of the receiver can be estimated regardless of the LED's and PDs' characteristics. The influences of tilted PDs on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…Finally, 62 new IPS works from 2018 with 5 or more citations [91,116,117,118,177,178,258,259,260,261,262,263,264,265,266,267,268,269,270,271,272,273,274,275,276,277,278,279,280,281,282,283,284,285,286,287,288,289,290,291,292,293,294,295,296,297,298,299,300,301,302,303,304,305,306,307,308,309,310,311,312] and 46 new IPS works from 2019 with 1 or more citations [105,313,314,315,316,317,…”
Section: Discussion On Ips Current Statementioning
confidence: 99%
“…Finally, 62 new IPS works from 2018 with 5 or more citations [91,116,117,118,177,178,258,259,260,261,262,263,264,265,266,267,268,269,270,271,272,273,274,275,276,277,278,279,280,281,282,283,284,285,286,287,288,289,290,291,292,293,294,295,296,297,298,299,300,301,302,303,304,305,306,307,308,309,310,311,312] and 46 new IPS works from 2019 with 1 or more citations [105,313,314,315,316,317,…”
Section: Discussion On Ips Current Statementioning
confidence: 99%
“…In table 1, a comparison between our works and previous experimental works of single LED VLP systems is presented. There are also other single LED VLP systems applying multiple tilted optical receivers [6], [47], but they require the targeted LED located in the field-of-view (FOV) of at least three tilted receivers. To keep the independence among different receivers, the tilted angle among those receivers can't be too small.…”
Section: -3mmentioning
confidence: 99%
“…A variety of techniques like On-Off Keying (OOK) or Square Wave Modulation [40], Orthogonal Frequency Division Multiple Access (OFDMA) [41], discrete tone multiplexing based on Intensity Modulation Direct Detection (IM/DD) [28], Optical Code Division Multiple Access (OCDMA) [42] have been utilized. It should be pointed out that simulation based studies have shown that by employing smartphones [43], fusion of multiple sensors [22], and tags containing multiple photo-sensors [44], it might be possible to localize a target while employing just a single visible luminaire. Multiple photodiode-based localization systems have also been reported in [21], [45]- [47].…”
Section: Related Workmentioning
confidence: 99%